Difficulties in Determining Investment Policies - Bates, George E. (The Review of Economics and Statistics, 1960)
George E. Bates, Difficulties in Determining Investment Policies, The Review of Economics and Statistics, Vol. 42, No. 3, Part 2. Higher Education in the United States: The Economic Problems (Aug., 1960), pp. 214-218